Maximal vs. explosive knee extensor strength in professional soccer players: inter-limb asymmetries and relationship with knee function - Cossich, V. R.; Gavilão, U. F.; Goes, R. A.; Perini, J. A.; Laett, C. T.; Maffiuletti, N. A. (European Journal of Sport Science, 2023)
The main aims of this study were to compare the magnitude of inter-limb asymmetry (ILA) and the relation with self-reported knee function between maximal and explosive knee extensor strength outcomes in professional soccer players. Forty-six male soccer players completed different maximal isokinetic and isometric contractions of the knee extensors for the assessment of maximal strength (peak torque and maximal voluntary contraction (MVC) torque) and explosive strength (early, intermediate, late, and peak rate of torque development (RTD)). Self-reported knee function was assessed with the International Knee Documentation Committee (IKDC) and Lysholm knee scoring scales. Peak torque and MVC torque showed comparable ILAs (8-9%), both being significantly lower than all RTD ILAs (16% on average; p < 0.001). ILAs for early RTD (21%) and peak RTD (19%) were significantly higher than all the other variables (p < 0.05). Only early and intermediate RTD were significantly correlated - though weakly - with both IKDC (rho = 0.32 for both) and Lysholm (rho = 0.36 and 0.30, respectively) scores. We conclude that explosive knee extensor strength - early RTD in particular - exhibited larger ILAs and better relations with self-reported knee function than peak torque and MVC torque in professional soccer players. These results confirm the validity and functional relevance of early RTD and the need for its inclusion in routine performance testing for soccer players.